Sensitive cell-based assay for determination of human immunodeficiency virus type 1 coreceptor tropism - Weber, Jan; Vazquez, Ana C; Winner, Dane; Gibson, Richard M; Rhea, Ariel M; Rose, Justine D; Wylie, Doug; Henry, Kenneth; Wright, Alison; King, Kevin; Archer, John; Poveda, Eva; et al. (Journal of clinical microbiology, 2013)
CCR5 antagonists are a powerful new class of antiretroviral drugs that require a companion assay to evaluate the presence of CXCR4-tropic (non-R5) viruses prior to use in human immunodeficiency virus (HIV)-infected individuals. In this study, we have developed, characterized, verified, and prevalidated a novel phenotypic test to determine HIV-1 coreceptor tropism (VERITROP) based on a sensitive cell-to-cell fusion assay. A proprietary vector was constructed containing a near-full-length HIV-1 genome with the yeast uracil biosynthesis (URA3) gene replacing the HIV-1 env coding sequence. Patient-derived HIV-1 PCR products were introduced by homologous recombination using an innovative yeast-based cloning strategy. The env-expressing vectors were then used in a cell-to-cell fusion assay to determine the presence of R5 and/or non-R5 HIV-1 variants within the viral population. Results were compared with (i) the original version of Trofile (Monogram Biosciences, San Francisco, CA), (ii) population sequencing, and (iii) 454 pyrosequencing, with the genotypic data analyzed using several bioinformatics tools, i.e., the 11/24/25 rule, Geno2Pheno (2% to 5.75%, 3.5%, or 10% false-positive rate [FPR]), and webPSSM. VERITROP consistently detected minority non-R5 variants from clinical specimens, with an analytical sensitivity of 0.3%, with viral loads of ≥1,000 copies/ml, and from B and non-B subtypes. In a pilot study, a 73.7% (56/76) concordance was observed with the original Trofile assay, with 19 of the 20 discordant results corresponding to non-R5 variants detected using VERITROP and not by the original Trofile assay. The degree of concordance of VERITROP and Trofile with population and deep sequencing results depended on the algorithm used to determine HIV-1 coreceptor tropism. Overall, VERITROP showed better concordance with deep sequencing/Geno2Pheno at a 0.3% detection threshold (67%), whereas Trofile matched better with population sequencing (79%). However, 454 sequencing using Geno2Pheno at a 10% FPR and 0.3% threshold and VERITROP more accurately predicted the success of a maraviroc-based regimen. In conclusion, VERITROP may promote the development of new HIV coreceptor antagonists and aid in the treatment and management of HIV-infected individuals prior to and/or during treatment with this class of drugs.
Keywords: HEK293 buňky; RNA virová; genom virový; Cyclohexanes; HIV Infections; Genotype; Humans; HIV infekce; Saccharomyces cerevisiae Proteins; tropismus virů; Receptors, HIV; fúze buněk; Cell Fusion; Maraviroc; env Gene Products, Human Immunodeficiency Virus; Receptors, CXCR4; Triazoles; lidé; HEK293 Cells; receptory CXCR4; látky proti HIV; Sensitivity and Specificity; Genome, Viral; HIV-1; receptory CCR5; Cell Line; genotyp; RNA, Viral; Viral Tropism; Anti-HIV Agents; cyklohexany; triazoly; pilotní projekty; maravirok; receptory HIV; buněčné linie; senzitivita a specificita; Pilot Projects; genové produkty env - virus lidské imunodeficience; Receptors, CCR5; Saccharomyces cerevisiae - proteiny